Effect of Counterions on the Soft Ionization Mass Spectra of Analytes with Multiple Permanent Charges - Kočková, Olga; Kasal, Petr; Zelený, Jan; Walterová, Zuzana; Vlčková, Věra; Jindřich, Jindřich (Analytical chemistry, 2024)
Multiply permanently charged analytes (MPCAs) are of great interest for various applications. MPCA soft ionization mass spectra (MS) strongly depend on the counterions of MPCA. We have studied thoroughly this effect to expand the use of MS in MPCA characterization. To this end, β-cyclodextrin-based MPCAs with 7 (MIM7NBCD) and 14 (MIM14BCD) quaternary ammonium charges with a series of monovalent counterions were prepared and their MS were measured using two of the most popular soft ionization techniques, electrospray ionization (ESI) and matrix-assisted laser desorption ionization (MALDI). MALDI MS of both analytes were well resolved, with signals assignable to the analytes only with the two least basic tested counterions (ClO4- and TfO-). Similarly, analyte-assignable signals were observed in ESI MS of MIM14BCD only with ClO4- and TfO-. The situation was opposite with ESI MS of MIM7NBCD where assignable signals were observed with Cl- but not with TfO-. Thus, to get high-quality MS, binding between the MPCA permanent charges and the counterions must be of the optimal effective strength, given also by the number of analyte permanent charges as shown by the simple combinatorial model of binding. Of practical interest is the observation that unsuitable counterions can be replaced in situ by an excess of corresponding acid. The findings form a coherent framework for interpreting and improving MPCA mass spectra.